Detection and epidemiology of bacterial canker (Pseudomonas syringae) on wild cherry (Prunus avium) - Luz, João Pedro Martins da (2011)
Submitted by Maria Eduarda Pereira Rodrigues (erodrigues@ipcb.pt) on 2011-12-15T17:08:27Z No. of bitstreams: 1 TD_JPL.pdf: 64257225 bytes, checksum: 27b429cf3f947a9ee5a2e0a62f301f80 (MD5)